Reading to learn anecdotal surveys in the college classroom - Romero, Angelita (2002)
Training in college reading has been one of the means of helping students find their way through college. A college reading program has come of age. To make it dynamic and functional for post secondary students it must be grounded on actual need of students -- in the context of a globalized age of technology and information.
Keywords: Literacy programs; Reading (Secondary)